How Children and Adults Represent God's Mind. (23rd March 2015) - Heiphetz, Larisa; Lane, Jonathan D.; Waytz, Adam; Young, Liane L.
Abstract: For centuries, humans have contemplated the minds of gods. Research on religious cognition is spread across sub‐disciplines, making it difficult to gain a complete understanding of how people reason about gods' minds. We integrate approaches from cognitive, developmental, and social psychology and neuroscience to illuminate the origins of religious cognition. First, we show that although adults explicitly discriminate supernatural minds from human minds, their implicit responses reveal far less discrimination. Next, we demonstrate that children's religious cognition often matches adults' implicit responses, revealing anthropomorphic notions of God's mind. Together, data from children and adults suggest the intuitive nature of perceiving God's mind as human‐like. We then propose three complementary explanations for why anthropomorphism persists in adulthood, suggesting that anthropomorphism may be (a) an instance of the anchoring and adjustment heuristic; (b) a reflection of early testimony; and/or (c) an evolutionary byproduct.